Manganese tolerance in Verbascum olympicum Boiss. affecting elemental uptake and distribution: changes in nicotinic acid levels under stress conditions - Erdemir, Umran Seven; Arslan, Hulya; Guleryuz, Gurcan; Yaman, Mehmet; Gucer, Seref (Springer Heidelberg, 2018)
A multielemental determination methodology in conjunction with an organic acid analysis that were supplemented with other stress parameters and an ultrastructural analysis used herein to study Verbascum olympicum Boiss. (Scrophulariaceae) under Mn stress. Uptake and accumulation characteristics of B, Cu, Fe, Mn, Mo, and Zn were evaluated in 8-week-old seedlings grown in Hoagland's nutrient solution and exposed to 5 (CK), 50, and 200 mu M MnSO4 for 7 days. Hydrogen peroxide levels were determined to evaluate oxidative stress, and changes in compatible substance levels (total phenolic contents, glutathione and glutathione disulfide levels) were determined to assess antioxidant defense mechanisms. The distribution of manganese on the root surface was characterized by scanning electron microscopy images and energy-dispersive X-ray spectroscopy analysis. The levels of nicotinic acid, which is involved in nicotinamide adenine dinucleotide biosynthesis, were determined in roots and leaves to assess tolerance mechanisms. V. olympicum exhibited the ability to cope with oxidative stress originating from excessive Mn, while increased Mn concentrations were observed in both roots and leaves. The translocation factor of B was the most affected among other studied elements under the experimental conditions. Total nicotinic acid levels exhibited a trend of reduction in the roots and leaves, which could be attributed to the appropriate metabolic progress associated with oxidative stress based on the nicotinamide adenine dinucleotide cycle that may reach glutathione in response to manganese stress during plant growth.
Keywords: Verbascum olympicum Boiss; Manganese stress; Element uptake; Hydrogen peroxide; Total nicotinic acid